Bioanalytical Method Development and Validation for the Estimation of Metoprolol in Human K2EDTA Plasma Using Liquid Chromatography Tandem–Mass Spectrometry - Meghana, Mungara (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2021)
Bioanalytical methods are widely used to quantitative determination of drugs and their metabolites in biological matrix such as plasma, serum, and urine and the methods could be applied to studies in areas of human clinical pharmacology, non-human pharmacology/toxicology studies (pre-clinical studies), and bioavailability and bioequivalence studies requiring pharmacokinetic evaluation. The major bioanalytical services are method development, method validation, and sample analysis. Bioavailability is defined as “The rate and extent (amount) of absorption of unchanged drug from its dosage form.” Bioavailability can be generally documented by a systematic exposure profile obtained by measuring drug/metabolite concentration in the systemic circulation over a particular time period. System suitability was performed by injecting six consecutive injections of metoprolol at higher concentration of calibration range. In conclusion, this work describes a very simple and sensitive liquid chromatography–mass spectrometry method for the determination of metoprolol suitable to monitor concentrations during clinical pharmacokinetic studies in humans.